DOMINANTS OF ECONOMIC DEVELOPMENT OF REGIONS OF THE NORTH CAUCASUS FEDERAL DISTRICT - L. Muratova; A. Demyanenko (Вестник Северо-Кавказского федерального университета)
The article deals with the essence, structural elements, measurement and utilization of development potential ofregional economies. On the materials of the regions of the North Caucasus Federal District, the peculiarities, trends and patterns of socio-economic condition and development are studied, key potential factors are studied, methodological approaches are developed and implemented to assess the levels of development potential of the studied subjects of the Federation, the efficiency of their functioning and the dominants offurther development. The group of regions of the North Caucasus Federal District on the potential of development has been carried out, the share of subjective factor in the formation of gross regional product has been determined.